Reaksi Pasar Atas Peristiwa Merger Bank Syariah BUMN (Studi Peristiwa BRI Syariah) - Diah Ayu Ariyani; Versiandika Yudha Pratama (Department of Islamic Banking, Faculty of Islamic Economics and Business, UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to determine the market reaction to the merger of state-owned Islamic banks (BNI Syariah, BRI Syariah and Syariah Mandiri) into Bank Syariah Indonesia (BSI). The market reaction is reflected in the abnormal return, trading volume activity, and security return variability. This research belongs to event study used in this study is secondary data obtained from financial reports published by BRI Syariah. The sample used in this study was BRI Syariah and the data analysis technique used the Sample Paired T-Test and the Wilcoxon Signed Rank Test. The results showed that there was no difference between abnormal returns and trading volume activity before and after the Islamic bank merger event. On the other hand, there are differences in security return variability before and after the Islamic bank merger event.